Synthesis of a 56 Component Library of Sugar β-Peptides - Lohse, A.; Schweizer, F.; Hindsgaul, O. (Combinatorial Chemistry & High Throughput Screening, 2002)
Many biological processes of vital importance are triggered by the molecular recognition of small carbohydrate units by proteins and receptors thus leading to the belief that carbohydrates could act as candidates for the design of new drugs. We have developed a new useful synthetic approach, which can be applied in a combinatorial manner, giving access to 1,1-di-substituted pyrans projecting amide side chains in both the α- and β-directions. Thus, treatment of the readily accessible hemiketal (1) with TFA followed by trimethylsilyl trifluoromethanesulfonate (TMSOTf) in the presence of a nitrile gives dihydrooxazinones (2) via a new type of modified intramolecular Ritter reaction. The dihydrooxazinones (2) can either be isolated or used directly in reactions with a broad variety of amines. Final deprotection furnishes the 1,1-di-substituted sugar β-peptides having the general structure (4).
Keywords: library of sugar